A Review of Local Anesthetic Systemic Toxicity Cases Since Publication of the American Society of Regional Anesthesia Recommendations: To Whom It May Concern. Issue 6 (November 2015) - Vasques, Francesco; Behr, Astrid U.; Weinberg, Guy; Ori, Carlo; Di Gregorio, Guido
Abstract : Abstract: Local anesthetic systemic toxicity (LAST) occurrence may cross several medical specialties. In 2010, the American Society of Regional Anesthesia and Pain Medicine (ASRA) published the first algorithm on LAST management, introducing the use of lipid emulsion (ILE) treatment. In the present study, we retrieved the cases of LAST published between ASRA guidelines dissemination and March 2014. We analyzed the reported clinical manifestations of LAST, characteristics of affected patients, onset time of toxicity, and clinical setting. We also focused on the treatment measures that were applied in the different cases, especially on the use of ILE and adherence to ASRA recommendations. Despite the limits of a review of case reports, the present study calls attention to the insidious nature of LAST, especially its atypical manifestations, and shows that ILE may currently be underadministered in daily clinical practice, especially in nonanesthesiology practice.